Application of the Two Stay Two Stray Learning Model in Improving Indonesian Language Learning Outcomes in Elementary Schools - Firman Firman; Nurul Aswar; Sukmawaty Sukmawaty; Mirnawati Mirnawati; Sukirman Sukirman (Universitas Cokroaminoto Palopo, 2020)
This study aims to determine the application of the Two Stay Two Stray learning model in improving Indonesian learning outcomes in grade V SDN 24 Temmalebba, Bara District, Palopo City. The research method applied was Classroom Action Research (CAR), with two cycles carried out in three actions. Furthermore, the results obtained by the students after implementing the guided writing strategy in cycle I were not yet complete, so it was deemed necessary to carry out further actions, namely, cycle II. Furthermore, in cycle II the skills of children in Indonesian language lessons increased significantly; the average score of students was 80. The results showed an increase in Indonesian learning outcomes.